THE IMPACT OF ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE THROUGH ENTREPRENEURIAL COMPETENCY AS MEDIATION VARIABLE: A STUDY ON SMES IN CULINARY SECTOR IN JAKARTA - Raymond, Yosafat; Selamat, Frangky (Graduate Program of Universitas Tarumanagara, 2023)
Enterprises with good business performance are enterprises that are able to survive in fast-moving market. In order to achieve maximum business performance, Small and Medium Enterprises (SMEs) need to have Entrepreneurial Orientation. This study aims to determine the effect of Entrepreneurial Orientation on business performance through Entrepreneurial Competency as a mediation variable among SMEs in culinary sector in Jakarta. The sample used in this study was 100 respondents who are owners of SME businesses in culinary sector in Jakarta. The sample selection technique used was purposive sampling and Smart Partial Least Square (PLS) software version 3.00 was used to make data analysis for this study. The results of this study indicate that innovation, risk taking and proactiveness (Entrepreneurial Orientation) have positive impact on business performance among SMEs in culinary sector in Jakarta.